Tamoxifen-induced hyperosmolar hyperglycemic state secondary to suspected pancreatic beta cell inflammation - Radovic, Billie; Cummings, Caitlyn; Presswala, Lubaina; Rosen, Ronald (Current problems in cancer. Case reports, 2020)
Selective estrogen receptor modulators, such as tamoxifen, have been used for many years to reduce the recurrence of breast cancer. There is limited data on tamoxifen use in males with breast cancer. Hyperglycemia or risk of diabetes is not listed on the package insert for tamoxifen. In this clinical case, one patient presented with hyperosmolar hyperglycemic state two months after starting tamoxifen for male breast cancer. Discontinuation of tamoxifen resulted in decreased hemoglobin A1c levels back to baseline and rebound of C- peptide levels.